Ethical and sociocultural challenges in managing dead bodies during epidemics and natural disasters - Suwalowska, H; Amara, F; Roberts, N; Kingori, P (BMJ Publishing Group, 2021)
Background Catastrophic natural disasters and epidemics claim thousands of lives and have severe and lasting consequences, accompanied by human suffering. The Ebola epidemic of 2014–2016 and the current COVID-19 pandemic have revealed some of the practical and ethical complexities relating to the management of dead bodies. While frontline staff are tasked with saving lives, managing the bodies of those who die remains an under-resourced and overlooked issue, with numerous ethical and practical problems globally. Methods This scoping review of literature examines the management of dead bodies during epidemics and natural disasters. 82 articles were reviewed, of which only a small number were empirical studies focusing on ethical or sociocultural issues that emerge in the management of dead bodies. Results We have identified a wide range of ethical and sociocultural challenges, such as ensuring dignity for the deceased while protecting the living, honouring the cultural and religious rituals surrounding death, alleviating the suffering that accompanies grieving for the survivors and mitigating inequalities of resource allocation. It was revealed that several ethical and sociocultural issues arise at all stages of body management: notification, retrieving, identification, storage and burial of dead bodies. Conclusion While practical issues with managing dead bodies have been discussed in the global health literature and the ethical and sociocultural facets of handling the dead have been recognised, they are nonetheless not given adequate attention. Further research is needed to ensure care for the dead in epidemics and that natural disasters are informed by ethical best practice.